HACKATHONS IN BRAZILIAN PUBLIC SECTOR: PURPOSES AND RESULTS FROM THE PERSPECTIVE OF PUBLIC AGENTS PROMOTING THE INITIATIVES - Ferreira, Gabriel de Deus; Farias, Josivania Silva (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
The public sector has been inviting citizens with programming skills (hackers) for marathons to propose digital solutions of collective interest, the hackathons. This research aimed to investigate the purpose and results of hackathon initiatives used as a strategy for open innovation in the Brazilian public sector, considering the public agents’ perspective regarding the initiatives. This is a qualitative, exploratory-descriptive study of multiple cases, based on document analysis and eight interviews. We identified 47 hackathons promoted until 2016 and observed an increase in the occurrence of such events. These initiatives main objectives in public sector are to create innovation, to promote social participation, to strengthen transparency and to bring actors closer to one another. As a weak spot, the low sustainability of the developed solutions was observed. A framework to promote hackathons in the public sector is proposed.